Inside men: confession, masculinity, and form in American fiction since the Second World War - McMaster, Iain George (The University of Edinburgh, 2018)
This thesis examines the use of form and spatial language in confessional fiction by men to elucidate how they conceptualise and negotiate material, corporeal, and psychological boundaries amidst the shifting social and political landscape of the United States since the Second World War. In light of increasingly urgent calls to address gender and racial discrimination in the United States, this study offers timely insight into an identity that, while culturally dominant, often escapes examination: white, heterosexual masculinity. Focusing on the representation of forms and spatial imagery, the chapters explore how five formally experimental novelists—Vladimir Nabokov, Joseph McElroy, Harry Mathews, William H. Gass, and Peter Dimock— employ the confessional genre to illustrate the way men perceive themselves as spatially and temporally circumscribed, and to look at the way they reinforce or transgress the boundaries of masculine identity. The post-war period in the United States witnessed a proliferation of confessional writing that coincided with the popularisation of Freudian psychoanalysis, the cold war rhetoric of suspicion, and the rise of second-wave feminism. As a result, the concept of the self increasingly becomes a repository for fantasies of potential discovery and hidden danger that rely, significantly, on metaphors of surface and depth. It is within, and often against, this cultural preoccupation with the self that these writers address, both directly and indirectly, the status of white masculinity. Drawing on innovative theories of forms and spatiality, this study examines the diverse language and imagery men use to describe their sense of selfhood as well as the bonds they form with others. The works considered in this study demonstrate a common preoccupation with the boundaries that separate interior from exterior and private from public. In response to pressures both intimate and impersonal, the narrators of the texts discussed in this thesis turn to confessional practices of written self-examination to locate themselves within networks of fluctuating relations and obligations. The question that this thesis seeks to resolve is whether the forms and spatial language the narrators employ enable or obstruct their efforts to negotiate the competing demands of ethical responsibilities to others and the desire to preserve a stable sense of self.
Keywords: confession; masculinity; form; spatiality; critique; American fiction; gender; Rita Felski; Caroline Levine; Vladimir Nabokov; Joseph McElroy; Harry Mathews; William H. Gass; Peter Dimock